Associations between Natural Ventilation for the Child's Bedroom during Night and Childhood Asthma in Shanghai, China. (2015) - Liu, Wei; Huang, Chen; Shen, Li; Wang, Xueying; Cai, Jiao; Zou, Zhijun; Chang, Jing
Abstract: From March 2013 to December 2014, we conducted a case-control study and inspected 454 residences with asthmatic or non-asthmatic children from six districts in Shanghai. Carbon dioxide (CO2 ) were passively measured 24 hours in the child's bedroom. We took the average concentration of CO2 during 00:00 to 06:00 as an indicator for the status of natural ventilation in the child's bedroom during night and investigated its association with childhood asthma. A total of 45.6% ( n = 203) residences had CO2 average concentrations higher than 1000 ppm . The mean CO2 concentration ± standard deviation was 1123 ± 741 ppm (range: 367 to 4595 ppm ). CO2 average concentrations in the residences measured in autumn and in summer were significantly lower than measured in winter. No significant differences were found among CO2 average concentrations among Case group and Control group in total and in different measured seasons. More deeply analyses were warranted.